Held - Michaels, Anne, 1958- (Alfred A. Knopf, 2023)
"A breathtaking and ineffable new novel from the author of the international best sellers Fugitive Pieces and The Winter Vault--a novel of love and loyalty across generations, at once sweeping and intimate. 1917. On a battlefield near the River Aisne, John lies in the aftermath of a blast, unable to move or feel his legs. Struggling to focus his thoughts, he is lost to memory as the snow falls--a chance encounter in a pub by a railway, a hot bath with his lover on a winter night. 1920. John has returned from war to North Yorkshire, near a different river. He is alive but still not whole. Reunited with Helena, an artist, he reopens his photography business and tries to keep on living. But the past erupts insistently into the present, as ghosts begin to surface in his pictures: ghosts with messages he cannot understand. So begins a narrative that spans four generations of connections and consequences that ignite and re-ignite as the century unfolds. In luminous moments of desire, comprehension, longing, and transcendence, the sparks fly upward, working their transformations decades later. Held is affecting and intensely beautiful, full of mystery, wisdom, and compassion, a novel by a writer at the height of her powers"--